The Influence of Reading and Writing Literacy and Reading Interest on Indonesian Language Learning Outcomes of Students at SMP Negeri 1 Kabanjahe - Ernawati Br. Barus; Vera Caroline Br. Barus (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to determine the influence of literacy and reading interest on the Indonesian learning outcomes of SMP Negeri 1 Kabanjahe students. The research was conducted with an ex post facto approach and a correlational descriptive design. The sample amounted to 150 grade VII students who were selected by proportional random sampling. Data is collected through questionnaires and value documentation. The results of the analysis showed that literacy had a significant effect on learning outcomes (r = 0.312; contribution 9.7%), as well as reading interest (r = 0.354; contribution 12.5%). Simultaneously, the two variables had a significant effect (R = 0.421) with a contribution of 17.7%. These findings show the importance of strengthening literacy and increasing reading interest in supporting Indonesian learning outcomes.